Biological Benefits of Diallyl Disulfide, A Garlic-Derived Natural Organic Sulfur Compound - Sonaji, Amle Vandana; Pradeep, Ade Rajkumar; Ganesh, Chapke Sima; Sambhaji, Dudhate Gitanjali; Anamika; Kumar, Roshan; Mziray, Amir Nurdini; Boateng, Edward Amoah; Nyarko, Richard Owusu; Boateng, Paul Owusu (Journal for Research in Applied Sciences and Biotechnology, 2024)
There is a possibility that diallyl disulfide and diallyl trisulfide can alleviate neuropathic pain in rats that have been subjected to CCI. The mechanisms by which these compounds alleviate pain entail an increase in the levels of H2S, BDNF, and Nrf2 in the sciatic nerve and the dorsal root ganglion (DRG). The use of garlic as a functional food and as a great source of pharmacologically active compounds is widely recognised and generally accepted. One of the most important bioactive components of garlic is called diallyl disulfide (DADS), and it possesses a number of beneficial biological effects. These capabilities include anti-inflammatory, antioxidant, antibacterial, cardiovascular protective, neuroprotective, and anticancer actions. In this review, the biological roles of DADS were reviewed in a systematic manner, and the molecular mechanisms that underlie these functions were explored. We have high hopes that this review will not only offer direction and insight into the existing body of literature, but will also make it possible for future study and the development of DADS for the intervention and treatment of other disorders.